Synthesis and property of alkyl dioxyethyl α-D-xyloside - Wu, Xiubing (J Mol Liq, 2020)
Due to the inherent defects of the long alkyl chain in the related hydrophilicity and water solubility, alkyl α-D-xylosides (7) had hardly the practical application as sugar-based surfactants and should be reconstructed to obtain alkyl dioxyethyl α-D-xylosides (5) with dioxyethylene fragment (−(OCH(2)CH(2))(2)-)) as the hydrophilic spacer to increase the related TPSA value. With D-xylose as the raw material, 1,2-cis alkyl dioxyethyl α-D-xylosides (5a-5f, n = 6–12) were stereoselectively synthesized. Their physicochemical properties including water solubility, surface tension, foamability, emulsification, thermotropic liquid crystal, and hygroscopicity had been investigated. Their water solubility was found to decrease gradually whereas their calculated HLB numbers were 14.72 → 11.67 (n = 6 → 12) with increasing alkyl chain length (n). Dodecyl dioxyethyl α-D-xyloside (5f) had not water solubility because the HLB number was low. Furthermore, their CMC values decreased with increasing the alkyl chain length, and the CMC value of decyl dioxyethyl α-D-xyloside (5e) was as low as 9.21 × 10(−5) mol·L(−1). Octyl dioxyethyl α-D-xyloside (5c) had the lowest surface tension (27.25 mN·m(−1)) at the CMC. Both of nonyl and decyl dioxyethyl α-D-xylosides (5d & 5e) possessed good foaming power and foam stability. Decyl dioxyethyl α-D-xyloside (5e) had the strongest emulsifying property either in the toluene/water system or in the octane/water system. Nonyl dioxyethyl α-D-xylosides (5d) had the most stylish S(A) texture. Hexyl dioxyethyl α-D-xyloside (5a) possessed the strongest hygroscopicity. Therefore, the alkyl dioxyethyl α-D-xylosides as a class of novel sugar-based surfactants will be widely considered as promising candidates for various practical applications.